NEUROMARKETING AND CONSUMER PERCEPTION MANAGEMENT - Mamatkulova Shoira Djalolovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Neuromarketing, an emerging interdisciplinary field combining neuroscience, psychology, and marketing, offers deep insights into consumer behavior by analyzing brain activity and physiological responses. This paper explores the mechanisms by which neuromarketing influences consumer perception, emphasizing how brands can manage and shape consumer experiences through emotional engagement, sensory stimuli, and subconscious decision-making processes. By leveraging neuroimaging tools such as fMRI and EEG, marketers can optimize advertising strategies and product positioning to align more closely with consumer desires and cognitive triggers. The ethical considerations and potential risks associated with this technology are also discussed, particularly regarding privacy and manipulation concerns. Understanding consumer perception through neuromarketing allows businesses to create more personalized and impactful marketing campaigns that resonate with their audience on a deeper, more intrinsic level.